An inexpensive modified weight-bearing device assembled in-house for high throughput unbiased behavioral pain assessment in mice. (October 2018) - Drackley, Brendan; Holtz, Matt; Yang, Jay
Graphical abstract: Abstract: Assessment of pain in rodents is essential for analgesic development and investigations of fundamental neurobiology of pain. We have previously reported on a modified weight bearing apparatus we call VASIC (voluntarily accessed static incapacitance chamber) enabling unbiased and high throughput assessment of pain in rats. The present report provides a detailed description of the construction of the apparatus with all necessary computer assisted design files for the printed circuit board and the plastic components, and the required software for controlling the data capture and data analysis hosted in an online source file repository to allow assembly of the device in-house at a cost affordable to most academic laboratories. We extend the application of the apparatus to assess weight bearing in mice to enable the use of genetic mice models to study pain.